2021
DOI: 10.3390/jcm10102054
|View full text |Cite
|
Sign up to set email alerts
|

Intracameral Bevacizumab Versus Sub-Tenon’s Mitomycin C as Adjuncts to Trabeculectomy: 3-Year Results of a Prospective Randomized Study

Abstract: Conjunctival wound healing determines success after filtration surgery and the quest for better antifibrotic agents remains active. This study compares intracameral bevacizumab to sub-Tenon’s mitomycin C (MMC) in trabeculectomy. Primary open-angle or exfoliative glaucoma patients were randomized to either bevacizumab (n = 50 eyes) or MMC (n = 50 eyes). The primary outcome measure was complete success, defined as Intraocular Pressure (IOP) > 5 mmHg and ≤ 21 mmHg with a minimum 20% reduction from baseline wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…[17][18][19] Despite bevacizumab been an efficient medication in controlling intraocular pressure the literature still reports that its efficacy is slightly lower than of mitomycin C in cases where both of the mediation are compared. 12,20 Similar results have been reported in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…[17][18][19] Despite bevacizumab been an efficient medication in controlling intraocular pressure the literature still reports that its efficacy is slightly lower than of mitomycin C in cases where both of the mediation are compared. 12,20 Similar results have been reported in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that average IOP and glaucoma medications decreased significantly in both groups at all follow-up points compared to baseline (p < 0.001), without significant difference between groups at 3 years. 20 Bilgic et al, compared the outcomes of trabeculectomy using two different routes of Bevacizumab administration as an adjunct in patients with primary open angle glaucoma. A significant reduction was observed in the IOP post trabeculectomy in all patients in both groups (paired t-test, P < 0.001, both groups), a change that had persisted at one-year follow-up.…”
Section: Kopsinis Et Al Compared the Effects Of Intracameralmentioning
confidence: 99%
“…40 Antitransforming growth factor β was tested but was no different to placebo. 41 The efficacy of other antifibrotics such as the anti-vascular endothelial growth factor agents [42][43][44][45] and the Ologen implant 46,47 need further study.…”
Section: Antifibroticsmentioning
confidence: 99%